Urgensi Sertifikasi Halal pada Produk Keuangan Syariah: Kajian Hukum Ekonomi Syariah terhadap Kepercayaan Konsumen - Syarifuddin Syarifuddin (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
The development of the Islamic financial industry in Indonesia has shown significant growth, both in terms of institutions, products, and public participation. However, public doubts remain regarding the level of Sharia compliance of these financial products. Halal certification is a crucial instrument for ensuring that a financial product truly complies with Sharia principles. This study aims to analyze the urgency of halal certification for Islamic financial products and its implications for consumer trust from a Sharia economic law perspective. The research method used is qualitative with a normative-juridical approach through a literature review of laws and regulations, fatwas from the National Sharia Council (DSN-MUI), and previous research findings. The results indicate that halal certification for Islamic financial products plays a strategic role in increasing transparency, accountability, and public trust. However, there is regulatory overlap between Law Number 33 of 2014 concerning Halal Product Assurance and the provisions of the Financial Services Authority (OJK). Therefore, harmonization of regulations and strengthening oversight by the Sharia Supervisory Board are crucial steps in ensuring the integrity of the Islamic financial system.